A Monument to Blackness: Murals and the Black Freedom Struggle - Jeffery, Hannah (2020)
This thesis offers the first in-depth analysis of black muralism across the US, from interior murals in the South, to street murals in the North and West. It argues that murals played a significant role in black communities at heightened moments of racial protest in the black freedom struggle because of their relationship with space. Focusing on 1930 to present day, I interrogate the currently missing connection between black politics, art, memory and space in studies of black muralism to uncover how murals created spaces of interaction within black communities. Recuperating black history and radical memory, and painting it onto building façades, muralists transformed walls of de facto segregated black communities into sites of education, ritual, performance and commemoration. This thesis traces the genealogy of black muralism throughout the black freedom struggle by uncovering how, why and when murals became interactive sites of black empowerment and imagination across the country at various moments of racial protest in the twentieth and twenty-first century.